'Western' professional ethics challenged by foreign acquisitions: German managers' patterns of interpretation surrounding Chinese and Indian investors. (October 2016) - Fuchs, Martina; Schalljo, Martin
Graphical abstract: Highlights: Initially, German managers welcome the new Chinese and Indian owners. Structural hermeneutics reveals conflicting patterns of interpretation. Such patterns are firmly rooted in the 'Western' professional ethics of managers. Managers' cosmopolitanism conflicts with different patterns of interpretation. During the post-merger process, managers distance themselves from their counterparts. Abstract: In times of globalisation managers are often involved in crossborder acquisitions. This contribution analyses how German managers interpret their new business partners after acquisition of their companies by foreign investors from China and India. At first glance, managers appear to extend a cosmopolitan welcome to the new owners. However, the methodology of structural hermeneutics reveals that the construal of managers of their foreign counterparts conflicts with sociocultural patterns of interpretation relating to legitimate leadership and functional administration. While regarding themselves as masters, the German managers also develop clear lines of demarcation in order to distance themselves from their international counterparts. The patterns of interpretation revealed in interviews are firmly rooted in the 'Western' professional ethics of managers, which becomes even clearer when analysing interpretations of 'Western' acquirers such as private equity investors. Economic geography can benefit from analysing how managers mobilise patterns of interpretation in a globalising world as such patterns reveal the limits of cosmopolitanism and the motives for lived practices of power within international organisations.